2020
DOI: 10.7150/thno.37472
|View full text |Cite
|
Sign up to set email alerts
|

ANKRD22, a novel tumor microenvironment-induced mitochondrial protein promotes metabolic reprogramming of colorectal cancer cells

Abstract: Background: The leading cause of poor prognosis in colorectal cancer (CRC) is the presence of colorectal cancer-initiating cells (CCICs). The interplay between the tumor microenvironment (TME) and CRC cells induces reacquisition of initiating cell characteristics, but the underlying mechanisms remain elusive.Methods: Candidate molecules were screened by global differential cDNA expression profiles of CCICs, which were enriched from patient-derived tumor xenograft models. Luciferase reporters and chromatin immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 53 publications
2
45
0
1
Order By: Relevance
“…ANKRD22 was widely expressed in the cytoplasm of cells in gastric pits and glands (Figure 1B). Consistent with the intestinal epithelium IHC results, 17 fluorescence colocalization in gastric SGC7901 and BGC823 cells indicated that exogenously expressed ANKRD22 was distributed almost completely in the mitochondria (Figure 1C). Western blot showed that both exogenous and endogenous ANKRD22 were located in purified mitochondria from gastric cancer cells and wild-type C57BL/6 mice gastric tissues.…”
Section: Expression Of Ankrd22 a Mitochondrialsupporting
confidence: 84%
See 2 more Smart Citations
“…ANKRD22 was widely expressed in the cytoplasm of cells in gastric pits and glands (Figure 1B). Consistent with the intestinal epithelium IHC results, 17 fluorescence colocalization in gastric SGC7901 and BGC823 cells indicated that exogenously expressed ANKRD22 was distributed almost completely in the mitochondria (Figure 1C). Western blot showed that both exogenous and endogenous ANKRD22 were located in purified mitochondria from gastric cancer cells and wild-type C57BL/6 mice gastric tissues.…”
Section: Expression Of Ankrd22 a Mitochondrialsupporting
confidence: 84%
“…We previously reported that ANKRD22 is not involved directly in the canonical Wnt-b-catenin pathway, but results in an increase in the intracellular concentration of Ca 2þ , suggesting that ANKRD22 may affect the canonical Wnt pathway via the noncanonical Wnt-Ca 2þ pathway for the repair of gastric mucosal damage. 17 To determine the relationship between the expression of ANKRD22 and the Wnt-Ca 2þ pathway, we first examined the changes in the intracellular levels of Ca 2þ in Ankrd22 -/mice 24 hours after gastric mucosal injury using the Fluo-4 dye. The Ca 2þ levels were significantly lower in the gastric mucosal epithelial cells of Ankrd22 -/mice than in those of Ankrd22 þ/þ mice (Figure 4C).…”
Section: Ankrd22 Deletion Suppresses the Noncanonical Wnt-ca 2þ Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Ankyrin repeat domain 22 (ANKRD22), a member of the ankyrin repeat (ANKR) family, is constitutively expressed in normal digestive tract epithelium and in tumor cells [7]. ANKR family proteins have been reported to play vital roles in cancer development and progression [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies have identified several mitochondrial genes as potential prognostic biomarkers. However, most studies lack a large-sample cohort, or rarely compare the genes expression between various subtypes of CRC, or the biomarkers have higher correlations with other tumors [ 12 16 ], which means more work still need to be done before clinical application.…”
Section: Introductionmentioning
confidence: 99%